ROPGAP3 interacts with PIN2 and modulates its clustering and trafficking in Arabidopsis - Kwang-Ho Maeng; Hyodong Lee; Hyung-Taeg Cho (Proceedings of the National Academy of Sciences, 2025)
Guanosine triphosphate (GTP)-hydrolyzing enzyme (GTPase) activating proteins (GAPs) negatively regulate small GTPase-mediated signaling by enhancing GTP to guanosine diphosphate (GDP) hydrolysis. The Rho small GTPase Of Plants (ROP) signaling pathway mediates the auxin-induced inhibition of endocytosis of PIN-FORMED (PIN) auxin efflux transporters. In our quest to find modulators of PIN behavior, we identified ROPGAP3 as a direct interactor of PINs in Arabidopsis . ROPGAP3 promoted PIN2 clustering, inhibited lateral diffusion and endocytosis, and reinforced its polarity even on loss- or gain-of-function conditions for ROP6 activity. In contrast, its close paralog ROPGAP1, adhering to ROP signaling, did not exhibit these characteristics. The specific molecular and cellular functions of ROPGAP3 also extended to developmental processes such as root gravitropism and lateral root formation. This study unveils a previously unrecognized role for GAPs beyond their traditional functions, providing insights into the mechanisms of protein clustering and plasma-membrane polarity reinforcement in plants.